مهارات الإدارة والقيادة الإدارية وأثرها على القوي العاملة الفدرالية في الولايات المتحدة الامريكية - دوة, ابوالقاسم سالم عبدالله (Al-Qurtas, 2025)
The purpose of this study was to reveal whether, the leadership and management skills within the U.S. federal workforce directly affect employee perception, which, in turn, is reflected in the political agenda of the presidential of the United States. Given the political structure of the organization, a shift in political office initiates change in the leadership of the organization. The significance of this study was to determine if the inclusive and participative approaches of the government seniors created a significant increase in the perception of organizational and management effectiveness based on the indicators in the leadership/climate assessment at the Department of Labor. The literature review examined the practices of organizational and management effectiveness and how it affected federal employees based on presidential influence. It also showed that the government adopts management trends from the private sector without understanding, at first, if they are adaptable to the federal government.